Agent takeover risk of principal in outsourcing relationships. (17th October 2010) - Bhimani, Alnoor; Hausken, Kjell; Ncube, Mthuli
The provision of outsourcing services creates relationships between knowledge vested with the supplier and the viability of outsourcing arrangements. Knowledge accumulation by the outsourcee can reach a level where it poses a market entry or takeover risk to the outsourcer. Knowledge translates into cash flows interpreted as asset values modelled as geometric Brownian motion accounting for uncertainty, drift, and volatility. We present this argument within a principal-agent theoretical perspective which embeds a real options analysis to represent risk growth. As an alternative to a complicated analysis of the benefits and costs to the agent and principal of a takeover, we propose that takeover of the principal by the agent can be expected if the agent's discounted cash flows is larger than the principal's discounted cash flows. The probability of the takeover of the principal's market by the agent is expressed as an 'optimal stopping time' probability problem.